Correlates of muscle dysmorphia symptomatology in natural bodybuilders: Distinguishing factors in the pursuit of hyper-muscularity. (September 2017) - Mitchell, Lachlan; Murray, Stuart B.; Hoon, Matthew; Hackett, Daniel; Prvan, Tania; O'Connor, Helen
Highlights: Eating disorder behaviors appear to increase risk of muscle dysmorphia symptoms. Evidence suggest pathological eating is central in muscle dysmorphia. Bodybuilders undertaking a rapid reduction in bodyweight may experience muscle dysmorphia symptoms. Novice bodybuilders may experience increased muscle dysmorphia symptoms. Abstract: Muscle dysmorphia (MD) is characterized by the pathological pursuit of muscularity and leanness, which includes eating- and exercise-related practices. The aim of this cross-sectional study was to identify correlations of MD symptomatology in natural bodybuilders. An online survey assessing diet, supplementation and training practices, and MD and eating disorder symptoms was completed by male bodybuilders with recent experience competing in a drug-tested competition. Sixty participants (age 29.6 ± 7.1 years) completed the survey. Eating disorder scores ( β  = .298), rate of pre-competition weight loss ( β  = .307) and number of competitions ( β  = −.257) were significant predictors of MD. The association between the EAT-26 and MDDI underscores the salience of disordered eating pathology in presentations of MD. Supporting this, greater rate of pre-competition weight loss, which may reflect disordered eating practices, is also associated with MD symptomatology. The inverse association of competition experience suggests novice bodybuilders may display increased MD symptomatology.